2021
DOI: 10.1029/2020jf006058
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Relationship Between Meander‐Bend Curvature, Sediment Supply, and Migration Rates

Abstract: Introduction 1.1. Background-River Meander Migration and Curvature River meander migration is one of the most ubiquitous processes shaping and redistributing mass on Earth's surface. The forms and patterns of river meander development have fascinated scientists since the early 20th century (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 79 publications
2
33
0
Order By: Relevance
“…In alluvial meandering rivers, high sediment loads favor a rapid accretion of the point bar at the inner bank, which forces erosion at the outer bank (bar push effects) and consequently enhances the annual migration rate (Constantine et al., 2014; Donovan et al., 2021; E. Eke et al., 2014). On the other hand, nearly clear water conditions associated with a scarce sediment supply facilitate a progressive incision of the channel bed, which causes outer bank instability and ultimately speeds up meander migration.…”
Section: Mechanisms Leading To Bank Retreatmentioning
confidence: 99%
“…In alluvial meandering rivers, high sediment loads favor a rapid accretion of the point bar at the inner bank, which forces erosion at the outer bank (bar push effects) and consequently enhances the annual migration rate (Constantine et al., 2014; Donovan et al., 2021; E. Eke et al., 2014). On the other hand, nearly clear water conditions associated with a scarce sediment supply facilitate a progressive incision of the channel bed, which causes outer bank instability and ultimately speeds up meander migration.…”
Section: Mechanisms Leading To Bank Retreatmentioning
confidence: 99%
“…Evidence of the course changes over the past 20 years also suggest that some of the sinuosity increase is by development of additional smaller loops and increased migration in low curvature zones (Figure 5). Research is in progress to examine the relation of rate of migration to curvature and the much‐debated question (Hooke, 2020) of non‐linearity and whether migration–curvature relations are linear monotonic (e.g., Donovan et all., 2021; Sylvester et al, 2019) or have a spatial autoregressive structure characterized by an exponential or oscillatory weighting function (Guneralp & Rhoads, 2009, 2010). The lack of evidence of acceleration of rate expected with meander development may well be that the bends are still in the relatively low curvature phases and there has been a lack of time since the planform resetting.…”
Section: Discussionmentioning
confidence: 99%
“…Ahmed et al (2019) and Constantine et al (2014) found that sediment supply is a key driving force of migration rate and that on Amazonian channels migration rate of meanders was lower with lower sediment supply. Donovan et al (2021) agree that sediment supply drives migration, though the migration–curvature relationship breaks down under low sediment supply. In terms of sediment supply, the evidence of deposition on bed, banks and floodplain in the Bollin reach is that sediment supply is abundant and that almost the whole sediment load here is sand and gravel; particle size analyses of floodplain sediment have confirmed this (Baird, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The formation of such surfaces most often occurs as the result of channel migration due to flooding (Cooper et al, 2003; Friedman & Griffin, 2017; Merritt & Cooper, 2000; Miller & Friedman, 2009; Schook et al, 2017; Scott et al, 1996), leading to the development of models relating forest establishment to various flow parameters (Benjankar et al, 2014; Mahoney & Rood, 1998; Scott & Friedman, 2018), but channel migration rates are also strongly affected by sediment load (Dean et al, 2016; Dean & Schmidt, 2013; Diehl et al, 2017; Donovan et al, 2021; Friedman et al, 2015; Merigliano et al, 2013; Naiman et al, 2010; Rathburn et al, 2018; Schook et al, 2017; Scott et al, 1996). Modeling (Dunne et al, 2010; Parker et al, 2011), experimental (Wickert et al, 2013), and observational (Constantine et al, 2014; Czuba & Foufoula‐Georgiou, 2015; Donovan et al, 2021) studies all show a strong influence of sediment load on channel migration rate, and models of river connectivity indicate that watershed locations of high sediment flux correspond to locations of rapid migration (Czuba & Foufoula‐Georgiou, 2015). Because channel migration rates are both a function of sediment load and play a considerable role in the creation of essential cottonwood establishment surfaces, we thus posit that the area of cottonwood forest established in a given time period is strongly influenced by the rate of delivery of sediment from upstream, an influence that can be readily observed by quantifying the area–age distributions of riparian cottonwood forests, which often serve to elucidate past channel geomorphic change (Everitt, 1968; Merigliano et al, 2013; Schook et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Many riparian trees in western North America, especially the dominant genus Populus (cottonwood), require wet, unvegetated sediment surfaces for successful establishment (Benjankar et al, 2014; Mahoney & Rood, 1998; Scott et al, 1996). The formation of such surfaces most often occurs as the result of channel migration due to flooding (Cooper et al, 2003; Friedman & Griffin, 2017; Merritt & Cooper, 2000; Miller & Friedman, 2009; Schook et al, 2017; Scott et al, 1996), leading to the development of models relating forest establishment to various flow parameters (Benjankar et al, 2014; Mahoney & Rood, 1998; Scott & Friedman, 2018), but channel migration rates are also strongly affected by sediment load (Dean et al, 2016; Dean & Schmidt, 2013; Diehl et al, 2017; Donovan et al, 2021; Friedman et al, 2015; Merigliano et al, 2013; Naiman et al, 2010; Rathburn et al, 2018; Schook et al, 2017; Scott et al, 1996). Modeling (Dunne et al, 2010; Parker et al, 2011), experimental (Wickert et al, 2013), and observational (Constantine et al, 2014; Czuba & Foufoula‐Georgiou, 2015; Donovan et al, 2021) studies all show a strong influence of sediment load on channel migration rate, and models of river connectivity indicate that watershed locations of high sediment flux correspond to locations of rapid migration (Czuba & Foufoula‐Georgiou, 2015).…”
Section: Introductionmentioning
confidence: 99%